Measurement of micro-channels with confocal microscopy - Prasanth Selvarajah. (2013)
In this report a proficient method is suggested to measure the geometric dimensions of a micro channel merged by a transparent top plate by employing the techniques of swift vertical scan of featured surfaces, detailed multi-layer sampling of depth response curves (DRC), and measurement of the refractive index of transparent top plate. The featured surfaces with profile fluctuation in the micro scale are scanned with high vertical resolution. The absolute height of each surface is determined by the highest point of the corresponding DRC. Since the DRCs are only sampled in the central area the processing speed is acceptable even with a large scanning length. The results of the measured depth should be corrected by the refractive index. The focal point moves at the same speed during the scanning motion, only in the same material. Any measurable steps on the sample surface can be used as the sampling area. By scanning the same area from both sides different sectional profiles can be extracted. The ratio of the different steps is the refractive index. Hence, this project aims to calibrate the refractive index and using that to correct the results acquired by internal scanning. This project will cover the literature review done on the project; it will then discuss the principle of 3D reconstruction based on confocal microscopy as well as the methods for individual scanning for featured surfaces and multi-layer DRC for absolute height measurement.